Caffeine alters the behavioural and body temperature responses to mephedrone without causing long-term neurotoxicity in rats - Shortall, Sinead E.; Green, A. Richard; Fone, Kevin C.F.; King, Madeleine V. (Sage, 2016)
Administration of caffeine with 3,4-methylenedioxymethamphetamine (MDMA) alters the pharmacological properties of MDMA in rats. The current study examined whether caffeine alters the behavioural and neurochemical effects of mephedrone, which has similar psychoactive effects to MDMA. Rats received either i.p. saline, mephedrone (10mg/kg), caffeine (10mg/kg) or combined caffeine and mephedrone twice weekly on consecutive days for three weeks. Locomotor activity (days 1 and 16), novel object discrimination (NOD, day two), elevated plus maze (EPM, day eight) exploration, rectal temperature changes (day nine) and prepulse inhibition of acoustic startle (PPI, day 15) response were assessed. Seven days after the final injection, brain regions were collected for measurement of 5-hydroxytryptamine (5-HT), dopamine and their metabolites. Combined caffeine and mephedrone further enhanced the locomotor response observed following either drug administered alone, and converted mephedrone-induced hypothermia to hyperthermia. Co-administration also abolished mephedrone-induced anxiogenic response on the EPM but had no effect on NOD or PPI. Importantly, no long-term neurotoxicity was detected following repeated mephedrone alone or when co-administered with caffeine. In conclusion, the study suggests a potentially dangerous effect of concomitant caffeine and mephedrone, and highlights the importance of taking polydrug use into consideration when investigating the acute adverse effect profile of popular recreational drugs.